The Basics of Stellites in Machining Perspective (International Journal of Engineering Materials and Manufacture, 2016)
Stellites are cobalt (Co)-based superalloys available in two main combinations: (a) a Tungsten (W) group with composition of Co-Cr-W-C, and (b) a Molybdenum (Mo) group containing Co-Cr-Mo-C. Stellites possess outstanding corrosion resistance, oxidation resistance, wear resistance, heat resistance, and low magnetic permeability. Components made of stellites work well in highly corrosive environments and maintain these advantageous properties at elevated temperatures. Components made of stellites are widely used in the oil and gas, automotive, nuclear power, paper and pulp, chemical and petrochemical, refineries, automobile, aerospace and aircraft industries. By virtue of their nonmagnetic, anticorrosive and non-reactivity to human body-fluid properties, stellites are used in medical surgery and in surgical tools, tooth and bone implants and replacements, heart valves, and in heart pacemakers. The hardness range of stellites is from 32 to 55 HRC, which makes stellites brittle materials but they have a low Youngâ€™s modulus. Due to their high hardness, dense but non-homogeneous molecular structure and lower thermal conductivity, machining operations for parts made of stellites are extremely difficult, categorising stellites as difficult-to-machine materials like Ti-alloys, inconels, composites and stainless steels. Usually, machine components made of stellites are produced by a deposition method onto steel substrates instead of expensive solid stellite bars. The rough surfaces of deposited stellites are then finished by grinding, rather than some other economic machining process, which is costly and time-consuming, making stellite products very expensive. This paper provides a basic overview of stellites applicable in engineering, their significances and specific applications, advantages and disadvantages in respect of machining processes.A brief review on experimental research on economically rational cutting parameters for turning operations of Stellite 6 using coated carbide inserts is presented in this paper. Interesting facts on the residual stresses induced by machining processes in Stellite 6 are revealed and analysed. The microhardness variation of machined surfaces of stellite 6 using different tool geometries is investigated in this research review.Â  It is revealed that coated carbide inserts with a medium-size nose radius perform better in respect of hardness changes and heat generation, producing minimum phase changes on machined surfaces of stellite 6.Â